Lift Net Fisheries an itâ€™s Continuity In Local Fishermen Community In North Sulawesi Province (Case study in Labuan Uki Bolaang Mongondow) - Ridwan Lasabuda; Lawrence J. L. Lumingas; Rose O. S. E Mantiri (Jurnal Ilmiah PLATAX, 2014)
Penelitian ini mendeskripsikan aktivitas kehidupan komunitas nelayan tangkap lokal yang beroperasi di kawasan teluk Labuan Uki, Kabupaten Bolaang Mongondow (pesisir UtaraÂ  perairanÂ  Sulawesi Utara, Laut Sulawesi). Dalam rangka mengungkap permasalahan yang dialami oleh nelayanÂ  lokal teluk Labuan Uki, metode yang digunakan dalam penelitian ini adalah metode survey, jenis studi kasus, dimana informasi dari responden (nelayan lokal teluk Labuan Uki)Â  dikumpulkan dengan menggunakan kuesioner, wawancara, pengamatan dan observasi.Â  Sedangkan metode analisis untuk menjawab tujuan penelitian yaitu analisis deskriptif. Adapun hasil yang ingin dicapai dalam penelitian ini adalah : 1) bagaimanaÂ  kondisi sosial ekonomiÂ  nelayan lokal Teluk Labuan Uki, Kabupaten Bolaang Mongondow; 2) tingkat produktivitas alat dan peralatan tangkap yang digunakan, serta jenis ikan tangkapan; 3) Mengetahui sistem pemasaran dan pengolahan hasil tangkapan ikan nelayan lokal Teluk Labuan Uki, kabupaten Bolaang Mongondow. Â  Keyword : nelayan lokal, alat tangkap bagan, teluk labuan uki Â  ABSTRACT This study was done to investigate the socio-economical conditions of the local fishermen of Labuan Uki Bay , Bolaang Mongondow ; productivity of tools and fishing equipment used and the type of fish catches and marketing systems, and processing of the catch . The method used in this study was a survey method , type of case study , which collected information from respondents using questionnaires, interviews, and observation. Methods of analysis to answer the research purpose was descriptive analysis. The results showed that socio-economical conditions of local fishermen ofÂ  Labuan Uki Bay were still low , where the majority of their houses were huts and made of wood ; the largest percentage of low educational level of elementary and secondary school . Fishing gear used was â€œbaganâ€ boat with a length of between 7-18 m, using an engine of 5.5 OD ( katinting ), and a net of 4.5 to 10 m depth, run by one person, usually done by the owner . The average of catching period was 12 hours per trip, starting from 18.00 PM until 06.00 AM, while the majority of fish caught were anchovy ( Stelopohorus spp ) . In peak season , the catch reaches 100 bowls ( 10 bowls = 1 kg ) per trip , while in the bad andÂ  transitional season ranged fromÂ  5 to 40 bowls per trip. Anchovy catches were dried using sun heat and placed on a rack , processed products were then sold to middlemen ( tibo - tibo ) at a price of Rp 15,000 per kg . There were some processed through boiling and then dried with a tool , and sold at Rp . 35.000 per kg . Keyword : local fishermen , â€œbaganâ€ fishing gear, Labuan Uki Bay